Struktur Kepemilikan Berpengaruh pada Kualitas Pelaporan Keuangan? - Kuntum Ayu Fadhilah; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2023)
This research aims to analyze the effect managerial ownership, and institutional ownership on financial reporting quality. This research uses a quantitative approach with a causal associative research type. The data used in this study are annual reports of sector transportation, utilities, and infrastructure sectors listed on the Indonesian Stock Exchange 2018-2020. Using purposive sampling method we obtained by 150 sample from 50 companies conducted observations from 2018 – 2020. This research using multiple linear regression analysis on the hypothesis testing. The result showed that the managerial ownership has a positive and significant effect on financial reporting quality and institutional ownership has a positive and significant effect on financial reporting quality.